Crystal structures of new layered perovskite-type oxyfluorides, CsANb2O6F (A = Sr and Ca) and comparison with pyrochlore-type CsNb2O5F - Yoo, Chung Yul; Kim, Jaegyeom; Kim, Sung Chul; Kim, Seung Joo (Journal of Solid State Chemistry, 2018)
New layered perovskite-type oxyfluorides, CsSrNb2O6F and CsCaNb2O6F, were prepared via solid state reactions and their crystal/electronic structures were compared to those of a compositional analogue, CsNb2O5F which has a 3-dimensional pyrochlore-type structure. The CsSrNb2O6F and CsCaNb2O6F phases are derived from the Dion-Jacobson family of a general formula A[A′n−1BnX3n+1] with n = 2. Rietveld refinements based on synchrotron X-ray diffraction data revealed that CsSrNb2O6F belongs to the tetragonal system with a = 3.86716(1) Å c = 11.45257(2) Å (P4/mmm, Z = 1), while CsCaNb2O6F adopts a 2ap × 2ap × 2cp superstructure with orthorhombic unit cell parameters, a = 7.64813(1) Å b = 7.67516(1) Å c = 22.43663(3) Å (Bmmb, Z = 8). The anion distributions in the lattices were confirmed by applying Bond Valence Sum (BVS) method; the F- ions occupy the central sites of the corner-sharing double perovskite block in the layered structures, but no ordering of anions was found in the pyrochlore structure. Through UV–Vis diffuse reflectance measurement, the band gap energy was estimated to 3.43 eV for CsSrNb2O6F, 3.65 eV for CsCaNb2O6F and 4.00 eV for CsNb2O5F. The band gap energy showed a good correlation with the Nb-O(F)-Nb bond angle(θ) in the oxyfluorides. As the Nb-O(F)-Nb bond angle deviates from 180° the value of Eg increase. The good linearity observed in the Eg vs. cos(180 - θ) plot suggests that Eg can be finely controlled by adjusting of the Nb-O(F)-Nb bond angle in the lattice.
Keywords: Crystal structure determination; Dion-Jacobson phase; Layered perovskite; Mixed-anion compounds; Oxyfluorides; Synchrotron x ray diffraction; Crystal structure determination; Dion-Jacobson phase; Energy band gap; Layered perovskite; Mixed-anion compound; Oxyfluoride; Synchrotron X-ray diffraction